Separate paths, same direction? De-standardization of male employment biographies in East and West Germany - Julia Simonson; Laura Romeu Gordo; Nadiya Kelle (Current Sociology, 2015)
Until the mid-1980s, labour markets in Germany were characterized by a high level of employment stability. Employment biographies of men were dominated by full-time employment in both East and West Germany and were hence quite similar in this respect, despite the two regions' enormously different institutional settings. Since that time however, important changes have occurred. Labour markets have become more flexible, as have employment biographies. However, the process towards de-standardization and increased discontinuity in employment biographies began in East Germany later than it did in the West. East German change started namely in 1990, when the German Democratic Republic was incorporated into the Federal Republic of Germany. This study uses the German Socio-Economic Panel (SOEP) to analyse how men's employment patterns in Germany have changed over three different birth cohorts. Through the use of sequence analysis the authors not only observe an increase of non-standard episodes in such biographies, such as unemployment and part-time work, but also investigate whether employment biographies have on the whole become more discontinuous in nature. In addition, the authors analyse the main differences in trends observed in East as opposed to West Germany as a result of differing societal and economic changes. The results of this analysis show evidence of de-standardization in employment in both regions. However, this trend follows a separate path in each region, with the process being faster in East Germany than in the West. – – Hasta mediados de la década de 1980, los mercados de trabajo en Alemania se caracterizaban por un alto nivel de estabilidad en el empleo. Las biografías de empleo masculinas eran dominadas por empleos de tiempo completo, tanto en Alemania Oriental cuanto en Alemania Occidental y eran, por lo tanto, bastante similares a este respecto, a pesar de los entornos institucionales enormemente diferentes de las dos regiones. Desde entonces, sin embargo, se han producido cambios importantes. Los mercados de trabajo se han vuelto más flexibles, al igual que las biografías laborales. Sin embargo, el proceso hacia la desestandarización y el el creciente aumento de la discontinuidad en las biografías laborales comenzó en Alemania del Este, antes que en la del Oeste. El cambio en Alemania Oriental comenzó alrededor de 1990, cuando la República Democrática Alemana se incorporó a la República Federal de Alemania. Utilizamos el Panel Socioeconómico Alemán (SOEP) para analizar cómo los patrones de empleo de los hombres en Alemania han cambiado a lo largo de tres cohortes de nacimiento diferentes. El uso de análisis secuencial nos permite no sólo observar un aumento de los episodios no estándar en este tipo de biografías, tales como el trabajo y el desempleo a tiempo parcial, sino también investigar si las biografías laborales, en general, tienden naturalmente a ser más discontinuas. También analizamos las principales diferencias en las tendencias observadas en el Este a diferencia de Alemania Occidental como consecuencia de diferentes cambios sociales y económicos. El resultado de este análisis es que se observa evidencia de desestandarización en el empleo en ambas regiones. Sin embargo, esta tendencia sigue un camino distinto en cada región, siendo el proceso más rápido en Alemania del Este que en el Oeste.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; cluster analysis; cohort comparison; de-standardization; employment biography; sequence analysis